Answer:
0.007
or
7 times 0.001
Step-by-step explanation:
B. 2 miles
C.2 1/2 miles
D. 3 miles
Answer:
3 miles
Step-by-step explanation:
no need
Answer:
C. 2 1/2
Step-by-step explanation:
ED2020
B)-2
C)15
D)40
Answer:
(c) For p = 15, leaves a remainder of -2 when divided by (x-3).
Step-by-step explanation:
Here, The dividend expression is = E(x)
The Divisor = (x-3)
Remainder = -2
Now, by REMAINDER THEOREM:
Dividend = (Divisor x Quotient) + Remainder
If ( x -3 ) divides the given polynomial with a remainder -2.
⇒ x = 3 is a solution of given polynomial E(x) - (-2) =
= S(x)
Now, S(3) = 0
⇒
or, p =1 5
Hence, for p = 15, leaves a remainder of -2 when divided by (x-3).
Answer:
Step-by-step explanation:
4
= (8 + 28)√10
= 36√10
Answer:
36
Step-by-step explanation:
Using the rule of radicals
× ⇔
Simplifying the radicals in the expression
=
= × = 2
=
= × = 4
Thus
4 + 7
= 4 × 2 + 7 × 4
= 8 + 28
= 36